Optimasi Perencanaan Pembangkit Listrik Tenaga Surya (PLTS) Terpusat Wilayah Pulau Terluar - Kristyadi, Tarsisius; Arfianto, Teguh (Infotekmesin, 2021)
Air Glubi Village which is one of the villages in the Bintan Pesisir sub-district, Bintan Regency, Riau Islands province, is one of the villages that is one of the outer islands of Indonesia which still has no electricity, and is difficult to reach by PLN. In this village, there is no water source available for PLTMH, so the alternative for electricity supply in Air Glubi Village is a centralized PLTS. This paper discusses the planning of centralized PLTS in Air Glubi Village, Bintan Pesisir sub-district, Riau Islands province. Because the availability of land, the economic capacity of the population is limited, optimization is needed. This optimization is used to get the optimum electrical energy output with these various limitations. From primary data, electricity demand in the village is 62492 Wh per day. The optimization resulted in a centralized PLTS design with an off grid type with a capacity of 37 kWp. The main component is a solar module made of monocrystalin with a capacity of 200 Wp each, totaling 186 modules. The battery uses VRLA 200 Ah each, totaling 250 batteries. The change of Dc electricity to AC is carried out by utilizing an inverter with a capacity of 10 kW totaling 4 pieces. To build a centralized PLTS in Air Glubi Village need costs Rp 2,983,902,171.